Review of Workplace Skills, Technology Adoption and Firm Productivity: A Review - Sid Durbin (New Zealand Government, The Treasury, 2004)
The way that skills contribute to productivity improvements in firms is still something of a "black box". There is general agreement that human capital (broadly defined) is important for growth. Less is known about the ways in which skills and knowledge contribute to a firm's pursuit of efficiency in production, the process of innovation and technology adoption, and to the take-up of market opportunities. This paper reviews literature on the types of skills utilised by firms, the mechanisms by which skills contribute to firm productivity, and how skills are acquired. It identifies potential policy implications relating to work based skills training.
Keywords: D21; D24; J24; L19; O30; 330; technological change; human capital; labour productivity; multifactor productivity; firm productivity; workplace productivity; skills